Change in cigarette dependence among a cohort of smokers following COVID-19 diagnosis in Kashmir valley: An observational follow-up study - Jeelani, Asif; Lone, Shafat Sideeq; Hilal Rather (Asian Journal of Medical Sciences, 2021)
Background: COVID-19 diagnosis should serve as an impetus for smokers to discontinue its use. The study was conducted to estimate the change in cigarette dependence among newly diagnosed COVID-19 cases. Aims and Objectives: COVID-19 diagnosis should serve as an impetus for smokers to discontinue its use. The study was conducted to estimate change in cigarette dependence among newly diagnosed COVID-19 cases. Materials and Methods: Study was conducted between October and December 2020 and newly diagnosed male COVID-19 patients who were current smokers at diagnosis were recruited from two hospitals involved in testing and treatment of COVID-19. Baseline socioclinical information was recorded at diagnosis in addition to the estimation of cigarette dependence using Fagerstrom Test for Nicotine Dependence (FTND) and health status using Post-COVID-19 Functional Scale (PCFS). Follow-up was done at 2 weeks after recovery using both FTND and PCFS scales. Wilcoxon signed-rank test, paired t-test, and ANOVA were used for univariate analysis and multivariate regression was done. Results: A total of 171 subjects with mean age of 43.79 years were included in the study. FTND scores decreased significantly from the day of diagnosis to follow-up visit with 79% of subjects reporting a decrease. On univariate analysis, decrease in FTND had a significant association with presence of comorbidity, any symptoms, presence of respiratory symptoms, and if supplemental oxygen was administered. On multivariate analysis, symptomatic COVID-19 disease, higher age, PCFS at baseline, and PCFS at follow-up had a significant association with decreased PCFS values at follow-up. Conclusion: COVID-19 diagnosis was followed by significant decrease in FTND score, particularly for symptomatic and older subjects. Post-COVID follow-up visits should be used asan opportunity by health providers to ensure its sustainability and for achieving cessation.